Identification and biological evaluation of thiazole-based inverse agonists of RORγt. Issue 9 (15th May 2018) - Gege, Christian; Cummings, Maxwell D.; Albers, Michael; Kinzel, Olaf; Kleymann, Gerald; Schlüter, Thomas; Steeneck, Christoph; Nelen, Marina I.; Milligan, Cindy; Spurlino, John; Xue, Xiaohua; Leonard, Kristi; et al.
Graphical abstract: Highlights: A new class of potent RORγt inverse agonists based on a thiazole core described. X-ray data (PDB ID 6CVH ) helped to elucidate the molecular mechanism. Compounds obtained with reduce off-target activities (RORβ and PXR activation). Compounds obtained with improved physicochemical and ADME parameters. Abstract: The nuclear receptor retinoic acid receptor-related orphan receptor gamma t (RORγt) is a transcription factor that drives Th17 cell differentiation and IL-17 production in both innate and adaptive immune cells. The IL-23/IL-17 pathway is implicated in major autoimmune and inflammatory diseases. RORγt lies at the core of this pathway and represents an attractive opportunity for intervention with a small molecule. Despite diverse chemical series having been reported, combining high potency and nuclear receptor selectivity with good physicochemical properties remains a challenging endeavor in the field of RORγt drug discovery. We describe the discovery and evaluation of a new class of potent and selective RORγt inverse agonists based on a thiazole core. Acid analog 1j demonstrated oral bioavailability in rats and was potent in a human whole blood assay, suggesting potential utility in treating autoimmune and inflammatory diseases such as psoriasis. X-ray crystallographic data helped to elucidate the molecular mechanism for RORγt inhibition with this series.